The use of environmentally friendly natural adhesives in the production of wood composite materials - Salabai, I. I.; Salabai, R. G. (Forestry Education and Science: Current Challenges and Development Prospects, 2024)
In order to find out the reasons for the formation of a bond between the adhesive and the glued material, the phenomenon of wetting wood with glue was analyzed; technological factors that characterize wood, glue and gluing conditions and their influence on the quality of the adhesive joint are also analyzed; the classification of natural adhesive materials according to various characteristics is given, the operational, technological, economic and ecological requirements for glues for wood composite materials are analyzed, the comparative characteristics of the properties of animal and vegetable glues are given; the use of adhesives of animal, vegetable and mineral origin in the production of wood composite materials is analyzed.